(untitled) (Research, Society and Development, 2025)
Streptococci are Gram-positive bacteria that cause various infections of the skin, mouth, lungs, and heart valves. Streptococcal pharyngitis is characterized by edema, epiglottis, and punctate abscesses of the tonsils, often accompanied by cervical lymphadenopathy, with the most common pathogen being group A β-hemolytic streptococcus (GAS). Myocarditis is a group of pathological entities in which infectious microorganisms or inflammation cause cardiac damage. Group A streptococcal tonsillitis (GAS) is an uncommon cause of nonrheumatic myocarditis. Most patients are treated with antibiotics, and some have received anti-inflammatory drugs. The overall objective of the present study is to elucidate the clinical, diagnostic, and histopathological findings of a patient diagnosed with myocarditis following streptococcal tonsillitis. The present study reported a case of myocarditis following streptococcal pharyngotonsillitis. The study showed a case in which the patient was successfully treated, the long-term consequences were minimized, the heart function was preserved, and the patient did not develop rheumatic fever, however, this is not always the case in similar cases. To prevent serious complications caused by upper respiratory infections caused by bacteria, the following are possible: educational activities for professionals and the community; training of professionals in their fields of activity; improvements in access to health services within the scope of the SUS; investments in material resources aimed at the diagnosis and adequate treatment of myocarditis; in addition to investments in research activities related to the subject.